Developmental lag of visuospatial attention in Duchenne muscular dystrophy. (January 2015) - Piccini, Giorgia; Gazzellini, Simone; D'Amico, Adele; Pane, Marika; Castelli, Enrico; Vicari, Stefano; Alfieri, Paolo
Highlights: The study extends our knowledge on voluntary and automatic attention skills in DMD. The study prove a developmental lag of both automatic and voluntary attention. Attention skills in DMD corresponds to a delay of about three years. Abstract: Children with Duchenne muscular dystrophy (DMD) present a specific deficit of voluntary attention but to date there has been no clear characterization of their attentional skills. The present study investigated the hypothesis that DMD patients present deficits of both voluntary and automatic visuospatial attention systems and that their performance could be equivalent to that of younger healthy males. Twenty males (mean age 10 years) with diagnosis of DMD, 20 age-matched healthy males (10 years 3 months) and 20 healthy younger males (7 years 6 months) were required to perform two visuospatial attention tasks: voluntary and automatic. In the voluntary task, the performance of the DMD group was significantly worse than that of the age-matched group, and equal to that of the younger controls. In the automatic attention task also, the performance of the DMD patients was less efficient than that of the age-matched controls and equal to that of the younger children. This study supports the previous report of voluntary attention deficit in DMD and extends the evidence to include also an automatic attention system deficit. The development level of attention in DMD patients is below that expected for their age and corresponds to a delay of about three years.